Determination of the oxidative stability and shelf life of anchovy (Engraulis engrasicholus l., 1758) fish burgers supplemented with garlic peel extract during cold storage: Effects of garlic peel extract on anchovy (Engraulis engrasicholus l., 1758) fish burgers - Fadiloğlu, Eylem Ezgi; Ucak, Ilknur (Progress in Nutrition, 2020)
The effect of garlic peel extract (GPE) on the quality of anchovy (Engraulis engrasicholus L., 1758) burgers during cold storage was investigated. GPE was able to prevent lipid oxidation compared to control, since the scores of PV, TBARS and pH of the burgers supplemented with GPE showed lower values. The lowest TVC and PBC values were observed in the burgers treated with GPE, especially in the burgers treated %4 GPE. Sensory results showed that the use of 2% and 4% garlic peel extract extended the shelf life of anchovy burgers for 3 days.